The Legal Protection of Auction Winners Execution of Mortgage Guarantee Auction - Agustina, Erika Putri (TABELLIUS: Journal of Law, 2023)
Legal Protection for the winner of the Mortgage Execution Auction means that there is a legal certainty regarding an object for the winner of the Mortgage Auction Execution.In the auction process that has been carried out, there will be legal consequences, namely the transfer of the rights of the auction object from the seller to the auction winner. In practice, the transfer of rights to the auction object raises a problem, such as the auction winner being unable to control the object because it is controlled by a third party. The empirical juridical approach is that this research means that in analyzing the problem it is carried out by combining legal materials (which are secondary data) with primary data obtained in the field, namely regarding "Legal Protection of the Rights of the Winner of the Mortgage Execution Auction.This study draws a conclusion that the provisions for purchasing land and buildings through auctions in Indonesia can be interpreted from the provisions of Article 1313 of the Civil Code and Article 1320 of the Civil Code regarding the terms of the validity of the agreement, then referring to Article 1 point 11 of Act No. 10 of 1998 concerning Amendments to Act No. 7 of 1992 concerning Banking, credit agreements do not always go well there are problems that arise, namely bad credit, to resolve the problem of bad credit then refer to Article 6 of Act No. 4 of 1996 concerning Mortgage Rights. Then it also refers to Article 1457 of the Civil Code regarding buying and selling.Keywords : Execution; Mortgage; Protection.